The Romanian Multimedia Theatre Dictionary – a Digital Historical Recovery Process: Project review: The Romanian Multimedia Theatre Dictionary - MARDALE, Cătălin (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
Besides an already troubled and uncertain background, the pandemic accelerated the need for digitization and digitalization as such. At the same time, from an optimistic perspective, it rushed this process in several areas. The lack of interest (and professionalism, we might say) for Romanian theatre’s archives has led to an unfortunate consequence: they are either very difficult to reach or they are buried inside the basement of a theatre or of a library and completely forgotten. In the last thirty years, no dictionary containing a coherent and systematic recent history of the Romanian theatre emerged.